A Scoping Review and Content Appraisal of Free Public Athlete Concussion Education Interventions - Julia D. Drattell; Emily Kroshus-Havril; Jennifer L. Gay; Robert C. Lynall; Julianne D. Schmidt (Journal of Prevention, 2026)
Abstract Health education relies on matching a program to users’ needs and preferences. Using programs aligned with expert recommendations may improve outcomes. The purpose of this study was to identify and assess free, public, concussion education programs for an athlete audience and provide context for users to select a program that fits their needs. We performed a rapid scoping review following JBI Methodology and Cochrane guidelines for programs published in English during the previous five years in PubMed or SportDiscus, or in grey literature. Education specifically for post-injury care and conference abstracts were excluded. We charted primary author/organization name, program name(s), date of publication or update, delivery method(s), option to provide a certificate of completion, and program content related to expert recommendations. The search identified 1,449 unique articles and programs, and after screening at the abstract and full-text levels, identified videos ( N = 6), online modules ( N = 4), in-person discussion guides ( N = 3), or fact sheets ( N = 2) that were created by 14 organizations published between October 2013 and April 2024. Six programs provided certificates of completion. Program content varied and no programs addressed all of the expert recommendations, but clear patterns emerged. The most common recommendations included were those specifically referred to as “content of concussion education for athletes”, being honest about symptoms throughout recovery, and athletes’ role in encouraging others to report a concussion. These findings identify programs to consider when selecting educational program(s), with different delivery methods and learning objectives. Future effectiveness-implementation research is needed to expand understanding of real-world applications and outcomes.